1992
DOI: 10.1176/jnp.4.3.239
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of FDG PET and IQNB SPECT in normal subjects and in patients with dementia

Abstract: Prior studies of patients with dementia have found similar qualitative patterns of cerebral glucose utilization with [18F]2-fluoro-2-deoxyglucose (FDG) PET and of putative muscarinic receptor activity with [123I]3-quinuclidinyl-4-iodobenzilate (IQNB). This raised doubts about whether receptor binding determines IQNB distribution and whether clinical information in IQNB scans is unique. To compare the methods directly, 4 normal volunteers and 7 patients with dementia underwent FDG PET and high-resolution IQNB S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Weinberger et al found that when 123 I-4-IQNB was used in SPECT, the brain region with strong binding to the muscarinic acetylcholine receptor was not correlated with the glucose metabolism intensity measured by FDG-PET, and the defect range was larger in AD patients. In patients with AD, the signal of the tracer showed differences in the expression of receptors in different brain regions (55).…”
Section: Targeted Neurotransmitter Tracers/probesmentioning
confidence: 99%
“…Weinberger et al found that when 123 I-4-IQNB was used in SPECT, the brain region with strong binding to the muscarinic acetylcholine receptor was not correlated with the glucose metabolism intensity measured by FDG-PET, and the defect range was larger in AD patients. In patients with AD, the signal of the tracer showed differences in the expression of receptors in different brain regions (55).…”
Section: Targeted Neurotransmitter Tracers/probesmentioning
confidence: 99%